2020
DOI: 10.19053/01217488.v11.n2.2020.10583
|View full text |Cite
|
Sign up to set email alerts
|

Patrones de uso de las plantas medicinales en el Chocó y Cauca (Colombia)

Abstract: En total se obtuvieron 1178 registros sobre el uso de plantas medicinales; 902 para el departamento del Chocó y 276 para el departamento del Cauca. Útiles en el tratamiento de 130 enfermedades o dolencias diferentes, asociadas a 17 categorías medicinales producto de la revisión bibliográfica de 17 publicaciones. Se encontraron 766 especies de plantas vasculares de las que 392 sp. para Chocó y 374sp. para Cauca, agrupadas en 132 familias. Las familias más representativas en el Chocó están: Gesneriaceae (103 uso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“… 180 In Colombia, medicinal plants have been essential for mestizos, indigenous and Afro-Colombians to treat multiple diseases, and during the COVID-19 pandemic they have been used to treat this disease. 181 …”
Section: Medicinal Plants For Covid-19 Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“… 180 In Colombia, medicinal plants have been essential for mestizos, indigenous and Afro-Colombians to treat multiple diseases, and during the COVID-19 pandemic they have been used to treat this disease. 181 …”
Section: Medicinal Plants For Covid-19 Treatmentmentioning
confidence: 99%
“…180 In Colombia, medicinal plants have been essential for mestizos, indigenous and Afro-Colombians to treat multiple diseases, and during the COVID-19 pandemic they have been used to treat this disease. 181 Flórez et al evaluated some plant extracts used in Colombia by indigenous and Afro-American people against SARS-CoV in vitro on the Vero E6 cell line. They reported that Gliricidia sepium inhibited SARS-CoV-2 in vitro by 75.6% at 10 mg/mL, and Piper tuberculatum reduced viral titer by 33.3% at 6 mg/mL after 48h.…”
Section: Medicinal Plants For Covid-19 Treatmentmentioning
confidence: 99%
“…Chinese medicine were utilized in about 91.5% of COVID-19 cases in China, showing encouraging results in improving the symptoms and reducing deterioration, mortality, and recurrence rates (13). In Colombia, medicinal plants play an important role in Afro-Colombian, mestizo, and indigenous territories treating different conditions, including COVID -19 (14,15). Plants as Gliricidia sepium, Piper tuberculatum, Solanum arboreum, Moringa oleifera, and Bocconia frutescens have been used within indigenous people given their multiple properties.…”
Section: Medicinal Plants Historically Used In Traditionalmentioning
confidence: 99%
“…Cordoba-Tovar et al reported that this plant is one of the species with the highest use against COVID-19 by western Colombian people (18). P. tuberculatum and, S. arboreum are recognized and used mainly in the Colombian Pacific region for their antimicrobial, analgesic, and antipyretic properties against several diseases (14,(19)(20)(21)(22), including COVID-19 despite the absence of scientific evidence. The potential of M. oleifera against SARS-CoV-2 has been explored recently by in silico approaches, finding flavonoid present on this plant showed good binding affinity, stable protein-ligand complexes, high binding energy, and similar binding poses in comparison with known SARS-CoV-2 Mpro inhibitor (23)(24)(25); its effect on COVID-19 associated coinfections has been explored as well (26).…”
Section: Introductionmentioning
confidence: 99%